Application of Realistic Mathematics Education Approach to Improve Understanding of Mathematics Concepts in Elementary Schools - Sesanti, Nyamik Rahayu; Jalmaf, Adrianus; Hari, Sri (Educare : Jurnal Penelitian Pendidikan dan Pembelajaran, 2025)
This research is motivated by the low interest and motivation of students in learning Mathematics, which has an impact on the lack of optimal understanding of concepts and learning outcomes, especially in data presentation materials. The purpose of this study is to determine the effectiveness of the application of the Realistic Mathematics Education (RME) approach in improving the understanding of Mathematics concepts of grade V students of SDN Bakalan Krajan 2 Malang. This study uses the Kemmis and McTaggart model Class Action Research (PTK) method which is carried out in two cycles. Each cycle consists of stages of planning, action, observation, and reflection. The research subjects amounted to 23 students. The data collection technique is carried out through a concept understanding test at the end of each cycle. The results of the study showed an increase in students' learning completeness from 82.60% in the first cycle to 91.30% in the second cycle. This improvement shows that the application of the RME approach is effective in helping learners better understand the concept of data presentation through the context of real situations that are close to daily life. These findings also confirm that realistic-based learning models can be an alternative to innovative strategies in Mathematics learning in elementary school.